From Inclusive Research to Inclusive Evaluation: Empowering People with Intellectual Disabilities to Shape the Services They Use - Garcia Iriarte, Edurne (My University, 2025)
This article explores how people with intellectual disabilities can be more involved in evaluating and regulating the services they use and the quality of their lives. Traditionally, these evaluations have been performed by professionals, but we argue that people with lived experience of intellectual disabilities bring unique insights and should be part of the process. The idea builds on ‘inclusive research’, where people with intellectual disabilities are not just subjects of research but active researchers. We use the term ‘inclusive evaluation’, to describe the active engagement of people with intellectual disabilities in inspecting and assessing services to ensure they meet standards and respect human rights. The paper describes a small exploratory study involving interviews with regulators, professionals, and people with intellectual disabilities across Ireland, Northern Ireland, Australia, and New Zealand who had been involved in inclusive evaluations. It found strong support for it, highlighting benefits such as greater trust and empathy during evaluations with users of services, more meaningful feedback for service providers, and increased confidence and employment opportunities for evaluators with disabilities. However, challenges remain, including funding and fair pay for the engagement of people with intellectual disabilities, training opportunities that meet the support needs of all stakeholders, and changing the cultural attitudes in support services that underestimate the abilities of people with intellectual disabilities. Steps to overcome these challenges are proposed such as piloting inclusive evaluation programmes, providing inclusive evaluation training to all involved, and lobbying governments to fund these roles. We conclude with a proposed implementation framework and a set of guiding principles that will nurture a spirit of inclusion and respect in service evaluations.
PUBLISHED
10.3390/socsci15010004
Keywords: inclusive research; intellectual disability; learning disability; inclusive evalu- ation; lived experience; training; attitude change; co-design; service assessment; policy change; cultural awareness; regulation; standards; Inclusive Society